Державне фінансове регулювання системи соціальних послуг - Насібова, Ольга Вікторівна (Видавничий дім "Гельветика", 2019)
У статті досліджено основні аспекти сучасного стану державного фінансового регулювання системи надання соціальних послуг. Виокремлено пріоритетність та посилення автономії місцевих органів влади та об'єднаних територіальних громад в організації, прийнятті управлінських рішень щодо планування та фінансового забезпечення якісних соціальних послуг. Проведено аналіз кількості діючих територіальних центрів соціального обслуговування, будинків-інтернатів та отримувачів соціальних послуг за 2010–2018 рр. Базові соціальні послуги згруповано за ознаками: превентивні/профілактичні; для осіб/сімей, що потрапили у складні життєві обставини; для осіб з інвалідністю та похилого віку; для дітей з інвалідністю; кризові послуги; для дітей-сиріт і дітей, позбавлених батьківського піклування. Окреслено механізми фінансового забезпечення системи надання соціальних послуг. Акцентовано увагу на першочерговості визначення потреб населення у соціальних послугах. Розглянуто соціальне замовлення як інноваційний напрям розвитку системи соціальних послуг.

An important component of the transformational transformations of the economic system is the continuation of innovations in the field of social services provision, which is caused by both internal factors of functioning of the social support system and external reasons. Innovation in the field of social services is the use of new mechanisms of financial security, modernization of the organizational model, the introduction of modern technologies of social work and best practices of service to the population. The introduction of social innovations should ensure a new quality solution to urgent problems of social involvement, full realization of economic activity of the population, improvement of quality of life. Despite some advances in the field of social service delivery, the early identification of people in need of social services and early intervention, the lack of effective mechanisms for strategic forecasting, planning and delivery of social services tailored to the needs of the individual, inadequate monitoring and evaluation mechanisms for the quality of social services, independent monitoring. In addition, social services that are not focused on preventing the emergence of difficult life circumstances do not form a reintegration into society, leading to the maintenance of a large number of such persons in inpatient residential care institutions, and consequently the right to live is not exercised. Particularly noteworthy is the imperfection of the financial support system for social services, which limits local governments to promoting de-institutionalization. The article explores the main aspects of the current state of state financial regulation of the social services delivery system. The priority and strengthening of the autonomy of local authorities and the united territorial communities in the organization, decision-making in planning and financial provision of quality social services are highlighted. The analysis of the number of existing territorial centers of social services, boarding schools and recipients of social services for 2010–2018. Basic social services are grouped by: preventive / preventive; for persons / families in difficult circumstances; for people with disabilities and the elderly; for children with disabilities; crisis services; for orphans and children deprived of parental care. The mechanisms of financial support of the system of providing social services are outlined. Emphasis is placed on prioritizing the needs of the population in social services. The social order is considered as an innovative direction of development of the system of social services.
State financial regulation of the system of social services
Keywords: фінансове регулювання; фінансове забезпечення; соціальні послуги; соціальне замовлення; соціальний захист; соціальні інновації; financial regulation; financial security; social services; social ordering; social protection; social innovation